[Afisz. Incipit] Zarządzenie w sprawie "Akcji czystości" ... / Piotr Nowak. - Nowak, Piotr (1921-?) ([wydawca nieznany], 1950)
Afisz informujacy o wiosennej akcji czystości 15-30.04.1950 r. w Sopocie.